ANALYSIS OF THE ROLE OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE IN THE RELATIONSHIP BETWEEN FINANCIAL BEHAVIORAL BIASES AND BITCOIN INVESTMENT DECISIONS AMONG GENERATION Z USERS OF TOKOCRYPTO AND INDODAX - Silvi Amisha Putri; Budi Rustandi Kartawinata; Agus Maolana Hidayat (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the role of perceived usefulness (PU) and perceived ease of use (PEOU) in mediating the relationship between financial behavioral biases—namely financial literacy (FL), overconfidence (OC), and risk tolerance (RT)—and Bitcoin investment decisions among Generation Z in Indonesia, using the Tokocrypto and Indodax platforms. Employing a quantitative approach with a survey of 360 active Generation Z investors, data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that financial literacy, risk tolerance, PU, and PEOU have a direct positive and significant effect on Bitcoin investment decisions. Overconfidence, however, showed no significant direct effect. Furthermore, PU and PEOU partially mediated the relationships between financial literacy and investment decisions, as well as between risk tolerance and investment decisions. Notably, PEOU emerged as the strongest mediating pathway, particularly for risk tolerance. Conversely, neither PU nor PEOU mediated the relationship between overconfidence and investment decisions. This research contributes theoretically by integrating Behavioral Finance theory with the Technology Acceptance Model (TAM) in the context of high-risk digital assets. Practically, it offers insights for platform developers to enhance user experience and design targeted financial education, and for regulators to formulate behaviorally-informed investor protection policies.